Psychological variables are better detectors of overtraining than physiological variables - Theriault, D.; Richard, D.; Labrie, A.; Theriault, G. (1997)
Measuring physiological variables does not seem useful in the detection of the overtraining syndrome when moderately high levels of stress and fatigue are encountered in the yearly monitoring of elite swimmers.